Arsenic toxicity following Ayurvedic medication - Shinde , Devyani; Bhattaram, Suhrith; Shinde, Varsha; Bhavsar, Sandeep (Indian Journal of Case Reports, 2024)
Alternative forms of medicine like Ayurveda have witnessed a rise in global popularity over the recent decades. Drugs used in Ayurveda, particularly those of mineral origin can lead to toxic effects due to heavy metal overdose. Here, we report the case of a 53-year-old woman who presented with glove-and-stocking paresthesia and scaly plaques following the institution of Ayurvedic drugs containing arsenic for dermatitis. She also had a loss of distal proprioception and a hyperesthetic response to pinprick. Her blood analysis showed elevated arsenic levels; 12 times the acceptable upper limit, with normal lead, cadmium, mercury, and chromium levels. The drug was immediately stopped and there was a gradual but incomplete resolution of the paresthesia and distal weakness over the next several months. The risk of heavy metal toxicity should be briefed to the patient before the start of mineral Ayurvedic drugs. Monitoring serum levels while on these medications might help identify toxicities early and can result in the commencement of therapy at an early stage.